CO₂ dissolution-diffusion in clay inhibitor/oil systems and synergistic CCUS-EOR effects in strongly water-sensitive reservoirs - Miaoxin Zhang; Jingchun Wu; Liyuan Cai; Bo Li; Xin Yu; Yangyang Hou; Fang Shi; Chunlong Zhang (Scientific Reports)
Abstract This study targeted a highly water-sensitive reservoir with high clay content (average 23.87%, mainly montmorillonite and illite), where waterflooding development induces hydration swelling of clay minerals, leading to pore-throat narrowing. The anti-swelling system and CO₂ were found to mitigate this phenomenon. The research investigated the dissolution, diffusion, and synergistic effects of CO₂ in the anti-swelling system/crude oil within the context of Carbon Capture, Utilization and Storage-Enhanced Oil Recovery (CCUS-EOR). Using the pressure decay method, core flooding experiments, microscopic visualization of oil displacement, and an improved mathematical model. We systematically investigated the influence of clay minerals on the balance between CO₂ storage and enhanced oil recovery (EOR). It was found that the diffusion coefficient of supercritical CO₂ increased rapidly and then levelled off with increasing pressure, which indicated that clay minerals hindered CO₂ diffusion. The anti-swelling system increases the effective pore connectivity by suppressing clay swelling, which increases the diffusion coefficient by 20–28%. The enhanced mathematical model combines the oil-water phase partition coefficients with the PR-EOS equation of state to accurately describe the multiphase interactions. The calculation results fit the experimental data by 92%, which is better than the traditional single-phase model. Through microscopic oil displacement experiments, core flooding tests, and quantitative analysis of full-cycle CO₂ saturation evolution. It is demonstrated that the sweep efficiency is anti-swelling system-CO₂ flooding is a higher sweep efficiency (73.95%) and achieves 58.12% oil recovery and 46.16% CO2 sequestration efficiency in a core with a permeability of 102.95 × 10−3 μm². The full-cycle CO2 saturation change rule was quantified, and the saturation cloud map was drawn. It is proven that the technology has the synergistic mechanism of ‘stabilising pore structure-reducing oil viscosity-efficient sequestration’, which combines significant oil recovery and carbon sequestration benefits, and provides theoretical and practical guidance for the low-carbon development of strong water-sensitive oilfields.